sistem dan aplikasi penentuan harga jual berdasarkan biaya total pada cv. terbit terang - Jatmiko, Prasetyo Budi; Widodo, Arifin Puji; Sukmaaji, Anjik (Jurnal JSIKA, 2014)
Since 1997, CV Terbit Terang had stood manufacturing in the printing and publishing house. During the company operates, in determining the selling price of the company using by basic estimates. The estimates of selling price is fourth or fifth times from the estimated cost of production per unit. This can be happen because the company estimates the determination of the selling price to cover other costs that are not identified in the manufacture of a product. Based on determination of estimated selling price, it be affected the CV. Terbit Terang sales and make sales figures decreased for 40%Â . This problem can be seen in the period 2008-2009The sales decline in the company can be overcome by application of selling price determination. The approach taken with the establishment of systems and applications to determine the selling price based on the total cost. Implementation of the method in this applications can give information desired profit. It will be obtained based on refund targets that have been invested from the calculation markup.Based on test , the applications is using data from CV. Terbit Terang, which made the system can determine the selling price to the total cost method. With the selling price is determined, then in subsequent periods CV. Terbit Terang obtain selling price based on the profits of the company targeted investment costs.